Humidification of high-performance and multifunctional polyimide/carbon nanotube composite foams for enhanced electromagnetic shielding. (November 2021) - Sun, Zhouping; Chen, Jiali; Jia, Xichen; Wang, Guoqing; Shen, Bin; Zheng, Wenge
Abstract: Though conductive polymer composite (CPC) foams have been investigated widely for electromagnetic interference (EMI) shielding owing to their low density and high EM absorption, fabricating high-performance CPC foams through a simple and easy-to-scale preparation process, as well as exploring new approach to achieve the shielding enhancement of CPC foams under mild conditions for meeting some special circumstances that needing higher shielding effectiveness (SE) in a short time, is still of great importance. In this work, multifunctional polyimide/carbon nanotube composite foams (PIF/CNT) were manufactured by the combination of effective chemical-foaming method and simple solution dip-coating approach. The resultant PIF/CNT with ultralow density exhibited the integration of excellent performances on absorbing-dominant EMI shielding with the extreme-temperature adaptability, flame retardancy, thermal insulation, infrared stealth and Joule-heating functions. On the other hand, the idea of humidifying-enhanced EMI shielding is proposed, and the EMI SE of wetted PIF/CNT samples can be massively improved due to the easy adsorption of strongly polar water molecules on the open-cell foam skeleton with hydrophilic poly (vinyl pyrrolidone). By the humidifying-drying cycles to enhance or restore the SE performance, our PIF/CNT material can be adjusted within a certain SE range to achieve intelligent electromagnetic response, providing another important guide for the design of novel intelligent EMI shields. Graphical abstract: Image 1 Highlights: Multifunctional PIF/CNT foams were manufactured by chemical-foaming method and solution dip-coating approach. The PIF/CNT foams exhibited excellent performances on EMI shielding, flame retardancy, thermal insulation, infrared stealth and Joule-heating functions. The humidifying-enhanced EMI shielding for PIF/CNT foams was proposed.